2015
DOI: 10.3389/fnhum.2015.00234
|View full text |Cite
|
Sign up to set email alerts
|

Altered resting-state EEG source functional connectivity in schizophrenia: the effect of illness duration

Abstract: Despite the increasing body of evidence supporting the hypothesis of schizophrenia as a disconnection syndrome, studies of resting-state EEG Source Functional Connectivity (EEG-SFC) in people affected by schizophrenia are sparse. The aim of the present study was to investigate resting-state EEG-SFC in 77 stable, medicated patients with schizophrenia (SCZ) compared to 78 healthy volunteers (HV). In order to study the effect of illness duration, SCZ were divided in those with a short duration of disease (SDD; n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
86
3
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(106 citation statements)
references
References 112 publications
14
86
3
3
Order By: Relevance
“…At least 3 minutes of clean EEG data (not necessarily consecutive) were selected and analyzed for each subject. According to previous exact Low-Resolution Electromagnetic Tomography software (eLORETA) studies [43,45,[62][63][64][65][66], artifact-free data were fragmented into epochs of 2 seconds for the EEG coherence analysis.…”
Section: Eeg Data Acquisition and Functional Connectivity Analysismentioning
confidence: 99%
“…At least 3 minutes of clean EEG data (not necessarily consecutive) were selected and analyzed for each subject. According to previous exact Low-Resolution Electromagnetic Tomography software (eLORETA) studies [43,45,[62][63][64][65][66], artifact-free data were fragmented into epochs of 2 seconds for the EEG coherence analysis.…”
Section: Eeg Data Acquisition and Functional Connectivity Analysismentioning
confidence: 99%
“…Evidences that contradict have been reported in fast oscillations at β (13-30 Hz) and γ frequencies at rest, including both elevated (Di Lorenzo, et al, 2015), reduced (Kam et al, 2013) and intact (Lehmann et al, 2014, Andreou et al, 2015, Tauscher et al,1998, Winterer et al, 2011 β frequency band connectivity. Preliminary evidence suggests that β based functional connectivity is influenced by illness progression and clinical symptomatology (Di Lorenzo, et al, 2015). For a systematic review tailored to functional connectivity evidences using EEG in schizophrenia see (Maran et al, 2016).…”
Section: Introductionmentioning
confidence: 95%
“…Interestingly, two studies reported a high correlation between functional connectivity at rest in α frequency band with symptoms in ScZ (Hinkley et al, 2011 ;Merrin and Floyd, 1996). Evidences that contradict have been reported in fast oscillations at β (13-30 Hz) and γ frequencies at rest, including both elevated (Di Lorenzo, et al, 2015), reduced (Kam et al, 2013) and intact (Lehmann et al, 2014, Andreou et al, 2015, Tauscher et al,1998, Winterer et al, 2011 β frequency band connectivity. Preliminary evidence suggests that β based functional connectivity is influenced by illness progression and clinical symptomatology (Di Lorenzo, et al, 2015).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Deficits in the auditory system have been associated with schizophrenia (Pfefferbaum et al, 1989;Polich, 2007;Roach and Mathalon, 2008;Mathalon et al, 2010;Decoster et al, 2012;Näätänen et al, 2012;Nagai et al, 2013;Bartha-Doering et al, 2015;Thibaut et al, 2015;Javitt and Sweet, 2015;Schall, 2016). Differences in cognitive processing have been revealed in visual paradigms too (Bestelmeyer, 2012;Oribe et al, 2014;Farkas et al, 2015), as well as during resting state (Greicius, 2008;Alonsosolís et al, 2015;Di Lorenzo et al, 2015). Quantifying the EEG amplitude during attentional tasks even allowed to identify patients with schizophrenia versus controls in 84.7 % of cases (Laton et al, 2014).…”
Section: Introductionmentioning
confidence: 99%